Increased Cytoplasmic Yes-associated Protein (YAP) Expression in Mismatch Repair Protein-Proficient Colorectal Cancer With High-grade Tumor Budding and Reduced Autophagy Activity. Issue 4 (April 2021) - Mikula, Michael; Najjar, Saleh; El Jabbour, Tony; Dalvi, Siddhartha; Umrau, Kavita; Li, Hua; Koo, Brandon H.; Lee, Hwajeong
Abstract : Yes-associated protein (YAP) is a transcriptional coactivator regulated by autophagy that stimulates colorectal cancer (CRC) progression through activation of epithelial-mesenchymal transition (EMT), represented by tumor budding. The associations between these components in CRC are unknown. Archived surgically resected CRCs with known mismatch repair protein (MMR) status were retrieved (n=81; 2010 to 2016). Electronic medical records were reviewed for clinicopathologic variables including pathologic TNM stage and clinical stage. Tumor budding was graded according to consensus guidelines. Cytoplasmic and nuclear YAP and p62 (autophagy substrate) immunoreactivity were semiquantitatively scored within tumor samples. The Student t test, Fisher exact test, χ 2 test, and Spearman correlation coefficient were performed with P <0.05 as a significance level. MMR proficiency (MMR-P) status correlated with high-grade tumor budding. The extent of cytoplasmic YAP staining and pathologic N stage was associated with tumor budding in multivariate analysis. Cytoplasmic YAP expression correlated with higher cytoplasmic p62 expression, suggesting an inverse correlation between autophagy activation and cytoplasmic YAP expression. Nuclear YAP expression correlated with pathologic N stage and clinical stage. A correlation between MMR-P status and tumor budding, combined with correlations between cytoplasmic YAP, tumor budding and p62 raise the possibility of 2 distinct neoplastic pathways concerning autophagy and YAP; one displaying relative activation of YAP and EMT, being commonly observed in MMR-P, and another with less active YAP and EMT, but active autophagy, being commonly seen in MMR-deficient CRC. Nuclear YAP staining could be useful in prognostication.